Complication of Early Banana Feeding in Neonates - E. M. Halimun; Joko Sunyoto; S. K. Hutomo; Oen L. H.; V. Yuwono (Indonesian Pediatric Society Publishing House, 2018)
Early introduction of banana in newborn babies is still practiced by many mothers from different areas throughout the country and gastric perforation due to phytobezoars are sttll a problem tn the country. During the years 1984 through 1991 at the Children and Maternity Hospital Harapan Kita jakarta, fifteen neonates were treated for gastric perforation among which 6 were due to banana bezoar, 6 were due to deject of the gastric muscle, 2 were due to necrotizing enterocolitis (NEC) and 1 was due to iatrogenic duodenal obstruction. Pathogenesis of gastric perforation due to phytobezoar and the macroscopic and histopathological appearance of the perforation and its differences with perforations due to other causes were discussed.